Vigorous Exercise Enhances Verbal Fluency Performance in Healthy Young Adults - Maya M. Khanna; Corey L. Guenther; Joan M. Eckerson; Dion Talamante; Mary Elizabeth Yeh; Megan Forby; Krystal Hopkins; Emmali Munger; Grace Rauh; Shringala Chelluri; Courtney Schmidt; Isabel Walocha; et al. (Brain Sciences)
Background/Objectives: We examined the effects of cardiovascular exercise on verbal fluency using a between-groups design. Methods: Within our experimental (i.e., exercise) group, participants performed phonemic and semantic verbal fluency tasks (VFTs) before, during, and after a vigorous 30 min bout of cycling. Participants within our control group also completed these VFTs before, during, and after a non-physical activity. We compared the VFT performance of the experimental (exercise) and control (no-exercise) groups of participants in terms of the characteristics of the words that they produced within the VFTs. In addition, we examined these aspects of VFT performance for each participant group across time within the experiment session. Conclusions: From these comparisons, we see that exercise influenced VFT performance. Most notably, participants engaged in exercise changed their VFT performance over time, while control group participants did not. Exercising participants produced more words over the course of their exercise session that contained fewer letters over time and were lower in frequency during and after exercise as compared to before exercise. Additionally, topic switches in the VFTs increased after exercise as compared to before exercise. Participants in the control group did not change their VFT performance over time according to any of these measures. These findings indicate that exercise impacted participants’ lexical access and that these VFT performance changes were not due to practice effects.